2019
DOI: 10.1017/s0007114519003040
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of growth hormone receptor-insulin-like growth factor 1 axis by dietary protein in young ruminants

Abstract: A reduced protein intake causes a decrease in insulin-like growth factor 1 (IGF1) concentrations and modulates Ca homoeostasis in young goats. IGF1 is synthesised by the liver in response to stimulation by growth hormone (GH). Due to rumino-hepatic circulation of urea, ruminants are suitable for investigating the effects of protein reduction despite sufficient energy intake. The present study aimed to investigate the impact of a protein-reduced diet on the expression of components of the somatotropic axis. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
(56 reference statements)
1
9
1
Order By: Relevance
“…Meanwhile, different animal species may have various adaptations of the change of dietary protein levels. In goat studies, it has been reported that young male goats fed a reduced-protein for 6-8 weeks significantly reduced plasma Ca concentrations due to reduced intestinal Ca uptake and microbial metabolism (34)(35)(36), which was inconsistent with our results. The difference may be related with the different physiological state of the experimental goats gone through.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, different animal species may have various adaptations of the change of dietary protein levels. In goat studies, it has been reported that young male goats fed a reduced-protein for 6-8 weeks significantly reduced plasma Ca concentrations due to reduced intestinal Ca uptake and microbial metabolism (34)(35)(36), which was inconsistent with our results. The difference may be related with the different physiological state of the experimental goats gone through.…”
Section: Discussioncontrasting
confidence: 99%
“…The possible reasons may be the abundant grass in the warm season, the average daily gain of the yak has been improved, and the growth and development of the animal body tend to mature with the increase in ADG, which gradually reduces the amount of protein synthesis in the body and increases fat deposition. Therefore, the role of GH is relatively weakened, and the serum GH concentration also decreases ( Firmenich et al, 2020 ). Serum triglyceride, total cholesterols, LDL, and HDL reflect the status or rate of lipid metabolism ( Huang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone is mainly produced by the anterior pituitary gland, secreted in a pulsatile manner and under direct control of hypothalamic neuronal projections ( Pombo et al, 2001 ), whose secretion is mainly regulated positively by growth hormone releasing hormone (GHRH), ghrelin ( Dimaraki and Jaffe, 2006 ; Khatib et al, 2014 ), and negatively by somatostatin (SS) ( Lu et al, 2019 ). Following release, the action of GH is achieved through binding with GH receptor (GHR), which is widely expressed in variety of tissues ( Møller and Jørgensen, 2009 ) and their interaction mainly results in the activation of JAK2/STAT5, MAPK-ERK1/2, PI3K-Akt, as well as PLC/PKC/Ca 2+ signaling pathways ( Zhu et al, 2001 ; Bocharov et al, 2018 ; Basu and Kulkarni, 2019 ; Chhabra et al, 2019 ) and the synthesis of IGF1 is mainly in liver ( Guevara-Aguirre et al, 2018 ; Zhang et al, 2019 ; Firmenich et al, 2020 ). In the GH signaling, GH binding proteins are produced at the cell surface and play complex roles, including modulate the half-life of plasma GH and the binding of GH to GHR ( Cawley et al, 2013 ).…”
Section: Somatotrophic System: a Brief Overview Of Structure And Physiological Functionmentioning
confidence: 99%
“…In most cases, the growth-promoting effects of GH depend on IGF1. In general, GH promotes IGF1 gene transcription and synthesis in the liver, thus regulating the circulating levels of IGF1 ( Guevara-Aguirre et al, 2018 ; Firmenich et al, 2020 ). Hypophysectomized rats show a rapid increase in serum IGF1 after recombinant human GH (rhGH) administration, and a 75% reduction of circulating IGF1 levels due to the liver IGF1-deficient in mice leads to a fourfold increase in GH secretion ( Yakar et al, 2004 ).…”
Section: Somatotrophic System: a Brief Overview Of Structure And Physiological Functionmentioning
confidence: 99%